GENDER ANALYSIS OF FAMILY LABOUR USE IN TRADITIONAL HAIR GOAT HUSBANDRY - H. Yilmaz; V. Demircan; M. Gul; M.C Örmeci Kart (Journal of Animal and Plant Sciences, 2014)
The main objective of this study was to determine the current family labour use patterns of farm households in hair goat farming systems using gender analysis. The study focused on investigating male and female labour use within the family in traditional hair goat farming activities by hair goat farming calendar. A survey was conducted using a face to face questionnaire with 92 hair goat farmers from 26 villages in Central, Atabey, Keciborlu, Egirdir and Sutculer districts of the Isparta province where there is intensive hair goat  farming. The farms were chosen by stratified random sampling method. The average household size was 4.75 members with the number of male (2.48) and female (2.27) respectively; in other words 52.18 per cent male and 47.82 per cent female.   It was also found that mean family labour use 14.70 h/daily, total average time spent by female and male in goat farming activities was 6.47 (55.99 per cent)  and 8.23 (44.01 per cent ) hour per day, respectively. Hair goat farming activities such as grazing, kid selling, barn disinfection, cheese selling, vaccination, bathing for mites, shearing, internal and external parasitical disinfection, are male dominated activities, whereas activities like milking and barn cleaning are female's domain and the rest of the activities were carried out both male and female.
Keywords: Family Labour use; gender analysis; hair goat farming; Turkey